2013
DOI: 10.1152/ajpcell.00242.2012
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 protects periodontal ligament

Abstract: Resolution agonists are endogenous mediators that drive inflammation to homeostasis. We earlier demonstrated in vivo activity of resolvins and lipoxins on regenerative periodontal wound healing. The goal of this study was to determine the impact of resolvin D1 (RvD1) on the function of human periodontal ligament (PDL) fibroblasts, which are critical for wound healing during regeneration of the soft and hard tissues around teeth. Primary cells were cultured from biopsies obtained from three individuals free of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 61 publications
2
48
0
1
Order By: Relevance
“…In a recent clinical trial, patients undergoing SRP taking a supplement with 300 mg/d of EPA + DHA had a lower mean PD, compared with those taking placebo (31). In vitro, resolvin D1, a downstream metabolite of DHA, has been shown to optimize healing of periodontal biopsies through downregulation of inflammatory mediators (50). Therefore, the consumption of fish or the use of v-3 FAs in conjunction with SRP should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent clinical trial, patients undergoing SRP taking a supplement with 300 mg/d of EPA + DHA had a lower mean PD, compared with those taking placebo (31). In vitro, resolvin D1, a downstream metabolite of DHA, has been shown to optimize healing of periodontal biopsies through downregulation of inflammatory mediators (50). Therefore, the consumption of fish or the use of v-3 FAs in conjunction with SRP should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…showed that the treatment of human periodontal ligament cells (PDL; a fibroblast-like cell) with RvD1, reduces cytokine induced production of the pro-inflammatory mediator prostaglandin E 2 , and up-regulates LXA 4 production. In addition, RvD1 significantly enhanced PDL proliferation, wound closure and fibroblast growth factor (FGF) release [36]. In another study, using a rat model of dorsal skin wound, Spite et al .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 At least 2 series of resolvins have been recognized: D-series resolvins are oxygenation products of docosahexaenoic acid (DHA) and E-series are synthetized from eicosapentaenoic acid (EPA). Resolvin D1 (RvD1) is among the best studied SPMs, promoting resolution after lung or kidney damage, 9,10 in periodontal diseases 11 and in allergic airways responses. 12 Moreover, RvD1 increases efferocytosis 13 by promoting an antiinflammatory/pro-resolving "M2-like" macrophage phenotype.…”
Section: Introductionmentioning
confidence: 99%